Successful and less successful interventions with youth and senior athletes: Insights from expert sport psychology practioneers - Henriksen, K.; Storm, L. K.; Stambulova, N.; Pyrdol, N.; Larsen, C. H. (Journal of Clinical Sport Psychology, 2019)
This study is focused on reflections of expert sport psychology practitioners about their interventions with competitive youth and senior elite athletes. Two objectives include: (1) to identify key structural components used by practitioners to describe sport psychology interventions and integrate them into an empirical framework, and (2) to analyze the practitioners` experiences in regard of their successful and less successful interventions in competitive youth and elite senior sport contexts using the empirical framework. We conducted semi-structured interviews with twelve internationally recognized sport psychology practitioners (SPPs) and analyzed the data thematically. The empirical framework derived from the SPPs` accounts contains eight structural components integrated into two categories: (1) the content and focus (with three components, e.g., adaptation of content), and (2) the organization and delivery of interventions (with five components, e.g., initiation and assessment of athletes` needs). Using the empirical framework we found differences between successful and less successful interventions and between youth and senior contexts in terms of needs assessment, adaptation and breadth of content, athlete-practitioner relationship, and intervention settings. The empirical framework might inform SPPs in their efforts to design, implement, and evaluate their services in these two contexts.